Molecular epidemiology of enterically colonizing Escherichia coli with resistance against third-generation cephalosporins isolated from stool samples of European soldiers with concomitant diarrhea on deployment in Western African Mali - Hoffmann, Katharina; Riediger, Matthias; Tersteegen, Aljoscha; Marquardt, Pauline; Kahlfuß, Sascha; Kaasch, Achim J.; Hagen, Ralf Matthias; Frickmann, Hagen; Zautner, Andreas E. (Frontiers in Microbiology, 2023)
Extended spectrum beta-lactamases (ESBL) are frequently found in Enterobacterales isolates from Western Africa. However, information on the molecular epidemiology of regional ESBL-positive Enterobacterales strains is scarce. In order to provide epidemiological information, ESBL-positive Escherichia coli isolates from stool samples of European soldiers with diarrhea deployed to a field camp in Mali were subjected to whole-genome sequencing (Illumina MiSeq and Oxford Nanopore MinION) and antimicrobial susceptibility testing. With two exemptions, sequence-based analysis suggested an absence of transmission events between soldiers as indicated by a high genetic diversity of isolates and sequence types, confirming previous rep-PCR results. Third-generation cephalosporin resistance was associated with the presence of blaCTX-M-15 genes with (n = 14) and without (n = 5) co-occurring blaTEM-1b genes. Between 0 and 6 virulence and resistance plasmids per isolate were recorded. The detected resistance plasmids could be categorized into five types, which, in turn, share different sequence-identical segments, representing particular antimicrobial resistance gene-associated mobile genetic elements (MGEs). Phenotypic resistance rates within the 19 assessed isolates that showed distinguishable colony morphologies were 94.7% (18/19) against ampicillin-sulbactam and trimethoprim/sulfamethoxazole, 68.4% (13/19) against moxifloxacin, 31.6% (6/19) against ciprofloxacin, 42.1% (8/19) against gentamicin, 31.6% (6/19) against tobramycin, and 21.1% (4/19) against piperacillin-tazobactam and fosfomycin. Virulence-associated genes mediating infectious gastroenteritis were rarely detected. The gene aggR, which is characteristic for enteroaggregative E. coli, was only detected in one single isolate. In summary, we found a variety of different strains and clonal lineages of ESBL-carrying E. coli. Transmission either between soldiers or from common contaminated sources was demonstrated in two cases and played only a minor role in this military field camp, while there were indications that resistance gene bearing MGEs had been exchanged between antimicrobial resistance gene-(ARG-)carrying plasmids.